Comparison of the MDRD Study and the CKD-EPI Study equations in evaluating trends of estimated kidney function at population level: findings from the National FINRISK Study - Juutilainen, Auni; Kastarinen, Helena; Antikainen, Riitta; Peltonen, Markku; Salomaa, Veikko; Tuomilehto, Jaakko; Jousilahti, Pekka; Sundvall, Jouko; Laatikainen, Tiina; Kastarinen, Mika (Nephrology, dialysis, transplantation, 2012)
There are no data comparing the Modification of Diet in Renal Disease (MDRD) Study and the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) Study equations in the evaluation of time-dependent trend of estimated glomerular filtration rate (eGFR) in the general population. Changes in eGFR and in the association of eGFR with kidney disease and cardiovascular disease (CVD) risk factors across age groups were estimated in two independent cross-sectional population surveys in Finland in 2002 and 2007 with 11 277 study participants, aged 25-74 years, using both the MDRD and the CKD-EPI equations. A trend towards decreasing eGFRs between the study years was observed using both equations, but the trend was more substantial when using the MDRD equation. The MDRD equation yielded lower estimates of eGFR than the CKD-EPI equation, with small mean difference between the equations at low eGFR level but substantial at the level of only mildly decreased or near-normal to normal kidney function. Decrease of eGFR was associated with an increase in CKD and CVD risk factors. However, an increase of risk factors was not observed among those who had mildly decreased eGFR by only the MDRD equation but not by the CKD-EPI equation. In comparison with the CKD-EPI equation, the MDRD equation augmented the trend of increasing prevalence of CKD, showed a weaker association with risk factors and tended to assign impaired renal function to individuals without an excess of cardiovascular risk factors.